A two-stage stochastic programming model for rail-truck intermodal network design with uncertain customer demand. Issue 3 (3rd April 2017) - Li, Shu-Xia; Sun, Si-Fan; Wang, Yi-Quan; Wu, Yi-Fan; Liu, Li-Ping
Abstract: With the globalization of supply chains, intermodal operations have become a key player in transportation. In real life, the consumer's demands are often uncertain. The recent literature is rich of papers that either emphasizes on uncertain customer demands or intermodal transportation planning. In this paper, we combine these two fields in order to identify new potentials for saving cost and improving the efficiency of intermodal logistics network. A two stage stochastic programming model was proposed to decide the terminal location and transportation routes under uncertain customer demands. And the AP data set is used to test the presented model. The result is compared with the traditional counterparts, which shows superiority in solution quantity under uncertain environment.